COMPARISON OF SOME BIOACTIVE COMPOUNDS OF FOUR MEDICINAL PLANTS - ABDULLAH, AWAZ FARUQ (Fırat Üniveristesi, 2022)
Bu çalışmada, dört tıbbi bitkide antioksidan aktivite, toplam fenolik içerik (TPC) ve Toplam flavonoid içeriği (TFC) ile bazı biyoaktif bileşiklerin belirlenmesi amaçlanmıştır. Bitkiler: Urtica dioica, Peganum harmala, Citrullus colocynthis ve Syzygium aromaticum karanfil teste tabi tutulmuştur. Bu çalışmada kullanılan ekstraksiyon tekniği, çözücü olarak metanol kullanarak maserasyon ekstraksiyonunu içermiştir. Elde edilen değerler TPC için 0,2-574 mg/g, TFC için 0,4 8,4 mg/g, FRAP için 11.3-484 mg/g ve 123-1979 mg/g MCC arasındadır. Ayrıca, elde edilen ekstreleri değerlendirmek için HPLC kullanıldı. Biyoaktif bileşikler HPLC – DAD cihazı kullanılarak belirlendi.

In this study, determination of the antioxidant activity, total phenolic content (TPC) and Total flavonoid content (TFC) as well as some bioactive compounds in four medicinal plants is aimed. The plants: Urtica dioica, Peganum harmala, Citrullus colocynthis and Syzygium aromaticum clove were subject to test. The extraction technique used in this study included maceration extraction by employing methanol as a solvent. The obtained values are between 0.2-574 mg/g for TPC, 0.4-8.4 mg/g for TFC, 11.3-484 mg/g for FRAP, and 123-1979 mg/g MCC. Further, HPLC was utilized to evaluate the extrcats obtained. THe bioactive compoubds were determined by using HPLC – DAD device.
Dört tıbbi bitkideki bazı biyoaktif bileşiklerin karşılaştırılması
Keywords: Kimya